Lean Six Sigma For Dummies - Morgan, John; Brenig-Jones, Martin (For Dummies, 2015)
Maximise the quality and efficiency of your organisation with Lean Six Sigma Are you looking to make your organisation more effective and productive? If you answered "yes," you need to change the way it thinks. Combining the leading improvement methods of Six Sigma and Lean, this winning technique drives performance to the next level-and this friendly and accessible guide shows you how. The third edition of Lean Six Sigma For Dummies outlines the key concepts of this strategy and explains how you can use it to get the very best out of your team and your business. The jargon-crowded language and theory of Lean Six Sigma can be intimidating for both beginners and experienced users. Written in plain English and packed with lots of helpful examples, this easy-to-follow guide arms you with tools and techniques for implementing Lean Six Sigma and offers guidance on everything from policy deployment to managing change in your organisation-and everything in between. Gives you plain-English explanations of complicated jargon Serves as a useful tool for businesspeople looking to make their organisation more effective Helps you achieve goals with ease and confidence Provides useful hands-on checklists Whether you want to manage a project more tightly or fine-tune existing systems and processes, the third edition of Lean Six Sigma For Dummies makes it easier to achieve your business goals.